The Relationship Between Nurses’ Knowledge and Surgical Site Infection (SSI) Prevention Practices at RSUP Tajuddin Chalid Makassar - Amalianti, Amalianti; Badaruddin, Badaruddin; Zaenal, Zaenal (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Surgical Site Infection (SSI) remains one of the major challenges in healthcare services worldwide. SSI is characterized by the presence of pus, inflammation, swelling, pain, and a warm sensation around the surgical wound. The high prevalence of SSI has become a major concern in efforts to improve healthcare quality and enforce stricter infection prevention standards. In Indonesia, the prevalence of SSI is estimated to range from 2.3% to 18.3%. Key factors in SSI prevention include improving healthcare workers’ adherence to aseptic procedures and implementing continuous training programs. This study aims to analyze the relationship between nurses’ knowledge and SSI prevention practices at RSUP Tajuddin Chalid Makassar. A quantitative research design with a descriptive correlational approach and cross-sectional method was employed. A total of 39 nurses were recruited using purposive sampling. The results showed that the majority of respondents (64.1%) had a moderate level of knowledge, while most (53.8%) demonstrated good SSI prevention practices. Fisher’s Exact Test revealed a significant association between nurses’ knowledge and SSI prevention practices (p = 0.018 < 0.05). This study contributes empirical evidence that nurses’ knowledge significantly influences infection prevention practices in surgical settings. It highlights the need for continuous education and structured training programs to strengthen compliance with aseptic standards. The findings provide practical implications for hospital policymakers and nursing managers in designing targeted interventions to reduce SSI rates and improve patient safety.